One Health and New Tools to Promote Health from a Holistic and Environmental Perspective (Revista Iberoamericana de Bioética, 2021)
SARS-CoV-2 exemplifies the close relationship between human, animal and environmental health. One Health goes beyond the biomedical concept of health to focus on the inter-connections between individuals, microorganisms, and ecosystems. Its application in healthcare governance is based on interdisciplinarity, the involvement of all sections of society, big data, artificial intelligence, and rigorous scientific data. One Health must be urgently adopted when restructuring development policies to make them more effective and sustainable, as well as protecting and promoting individual and collective health in the broadest bioethical sense, as advocated by Jahr or Potter and fully in line with the 2030 Agenda.
Keywords: bioethics; One Health; sustainability; promoting health; ecosystem